Study of Some Morphometric Features and Feeding Habits of Cyprinus Carpio (Linnaeus, 1758) and Coptodon Zillii (Gervais, 1848) Collected from Tigris River, Iraq - Ghazwan , Mohammed I.; Jassim, Suhad Y.; Makawi, Zainab A. (Technium BioChemMed, 2021)
The present study attempts to identify the relationship between some phenotypic measurements of the two species , Common carp Cyprinus carpio and Coptodon zillii, and the feeding habits of these two different species in terms of mouth shape, mouth depth and some of the vital characteristics of these two species related to the way they feed, especially total Length and weight, in the Iraqi inland water environment, specifically from the Tigris River.